Utilization Of Betel Leaf (Piper betle Linn.) and Lantana camara Leaf Extracts As Botanical Insecticides For Armyworm ControL (Spodoptera litura) - Idum Satia Santi; Emmy Hamidah; Agus Manto (Akademi Komunitas Perkebunan Yogyakarta, 2026)
The extensive use of synthetic insecticides has led to environmental contamination, pest resistance, and adverse effects on non-target organisms. Botanical insecticides provide a safer alternative for sustainable pest management. This study evaluated the insecticidal activity of betel leaf (Piper betle L.) and Lantana camara leaf extracts against armyworm (Spodoptera litura). A laboratory bioassay was conducted using three extract concentrations (30%, 40%, and 50%) arranged in a completely randomized design. Larval mortality was recorded daily for seven days after application and analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Both botanical extracts significantly increased larval mortality over time. Mortality began to rise on the second day and increased sharply on the third and fourth days after application. By the fifth day, all extract treatments resulted in nearly 100% mortality, while no mortality occurred in the control. Cumulative mortality patterns indicated that Lantana camara induced a faster initial lethal effect, whereas Piper betle showed a slightly delayed but equally effective response. No significant differences were observed among concentrations, indicating that a 30% concentration was sufficient for effective control. These results highlight the potential of betel leaf and Lantana camara extracts as effective botanical insecticides for armyworm management.